Study of Psychological Factors of Young Consumers of Odisha (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2018)
Every consumer when purchases a product or when in the decision making phase for purchasing  a product passes through some process of mental decision comprising of the choice sets to reach  at the correct decision. As a general practice, apart from the information gathering about the  product, the decision making i.e. mental process are influenced by psychological variables also.  This paper aims at finding the psychological factors of young consumers of Odisha. Exploratory  factor analysis is carried out using the psychological variables from drfferenl consumer psychological  studies to find out the psychological factors of the young consumers of Odisha. In this study four  psychological factors emerged such as first one is 'Materialism' factor which depicts the materialistic  psychological dimension of the consumers. Second one is 'Susceptibility to Interpersonal Influence'  factor which describes the psychological characteristics of consumers where there is consumers'  susceptibility to the interpersonal influence. Third factor is 'Opinion Leadership & Self Confidence'  where the factor represents the shopping opinion leadership of the consumer and self-confidence  as well and the fourth Factor is 'Perceived Time Pressure' which depicts about the perceived time  pressure of the consumer. These psychological factors will help in understanding the consumer  decision making and behaviour.
Keywords: Materialism; Time pressure; Self-confidence; Interpersonal Influence; Psychological factor